How much further for the sub-2-hour marathon? - Sousa, C. V.; Sales, M. M.; Nikolaidis, P. T.; Rosemann, T.; Knechtle, B. (Open Access Journal of Sports Medicine, 2018)
The sub-2-hour marathon is a new barrier in endurance running performance, and it has been widely debated in the scientific community. In this review we present a mathematical model to estimate the possible year when a male could break through the sub-2-hour barrier, and also an estimation of when a female could break Paula Radcliffe`s marathon running record. Further, we present several aspects (ie, physiology, nationality, age, biomechanics, pacing, and drafting) that are associated with marathon running performance in elite runners and, finally, the possible characteristics of the male to break the sub-2-hour barrier. In summary, with the results of the developed equations, it is possible that a male athlete can break through the sub-2-hour barrier in the next decade (with Nike® Breaking2 performance 1920-2018 [NBP]: y =0.0417x2-14.18x +3,128; year of 2026; without NBP 1920-2018: y =0.045x2-15.12x +3,194; year of 2027). This marathoner will possibly have a maximal oxygen uptake >85 mL·kg-1·min-1 and should perform the race at a pacing higher than 85% of maximal oxygen uptake. In addition, this runner should pay more attention to strength training, endurance strength, speed training, and focus on running training at an intensity above the anaerobic threshold. Most likely, this runner originates from East Africa (especially from Ethiopia) and will have an age of ~27 years. For the females, there is poor evidence regarding the physiological profile of the female marathoner who will break Radcliffe`s record, but the available literature suggests that it will not happen any time soon.